(untitled) (Research, Society and Development, 2021)
Suicide is a multi-determined problem, both individual and public health. Therefore, it involves different prevention and treatment procedures for the bereaved. In this last item is the concept of post-invention, which consists of psychological help strategies for family members, friends and acquaintances of suicidal people for a better elaboration of grief, thus avoiding new disorders and complications. Academic research on postvention is still scarce. Especially with regard to quantitative procedures, such as those that use psychometric questionnaires, which aim to measure psychological constructs involved. Faced with this problem, this research aims to raise how Psychometry has been used to support interventions in postvention. To accomplish this objective, a systematic review of publications was undertaken, followed by bibliometric analysis of the selected papers. The main results of the research are: a) a selection of the most relevant surveys about Psychometrics in postvention around the world; b) the analysis of the psychological constructs that are the focus of attention; c) a criticism of the concept of postvention in light of the psychometrics.